Răspunsuri

2014-05-18T19:59:06+03:00
A) ⇒=(4x²+1)(4x²-1)=(4x²+1)(2x-1)(2x+1)
b)⇒=(x²y²-9)(x²+y²+9)=(xy-3)(xy+3)(x²y²+3)
c)⇒=(a²-2)(a²+2)
d)⇒=[(x+1)²-4][(x+1)²+4]=[(x+1)-2][(x+1)+2][(x+1)²+4]=(x-2)(x+3)[(x+1)²+4]
a) ⇒=(4x²+1)(4x²-1)=(4x²+1)(2x-1)(2x+1)
b)⇒=(x²y²-9)(x²+y²+9)=(xy-3)(xy+3)(x²y²+3)
c)⇒=(a²-2)(a²+2)
d)⇒=[(x+1)²-4][(x+1)²+4]=[(x+1)-2][(x+1)+2][(x+1)²+4]=(x-2)(x+3)[(x+1)²+4]
2014-05-18T21:18:21+03:00
a) ⇒=(4x²+1)(4x²-1)=(4x²+1)(2x-1)(2x+1)
b)⇒=(x²y²-9)(x²+y²+9)=(xy-3)(xy+3)(x²y²+3)
c)⇒=(a²-2)(a²+2)
d)⇒=[(x+1)²-4][(x+1)²+4]=[(x+1)-2][(x+1)+2][(x+1)²+4]=(x-2)(x+3)[(x+1)²+4]